Оптимизация комплексного показателя надежности радиотехнических устройств путем изменения их топологии - Uvarov, B. M.; Zin'kovs'kii, Yu. F. (PE "Politekhperiodika", Book and Journal Publishers, 2015)
The authors consider problems of determination of reliability parameters for designs of radio engineering devices (RED) under the influence of mechanical and thermal (external and internal) factors. Mechanical factors (linear acceleration, vibration, impact) cause mechanical effect on the outputs of elements of electronic structure (EES) and soldered connections, which can result in decrease of reliability. External thermal effects and internal heat release in the elements of the electronic structure of radioelectronic devices raises the temperature of these elements, thereby reducing the reliability not only of the elements, but of the device as a whole. The paper presents the methods for determination of versatility indicators of reliability depending on mechanical and thermal effects on REDs. Optimization of configuration of the cell (topology) using computer programs allows reducing mechanical and thermal effect on the outputs of EESs and to obtain maximum parameters of reliability of a design. The optimum topology of a cell obtained by such program is illustrated. As a result of optimization, reliability of cells has increased.